Genetic and chemical diversity of Uncaria tomentosa (Willd. ex. Schult.) DC. in the Brazilian Amazon - Gomes Honorio, Isabela Cristina [UNESP]; Bertoni, Bianca Waleria; Campos Telles, Mariana Pires de; Braga, Ramilla dos Santos; Franca, Suzelei de Castro; Coppede, Juliana da Silva; Conde Correa, Valeria Siero; Felizola Diniz Filho, Jose Alexandre; Soares Pereira, Ana Maria (Public Library Science, 2017)
Uncaria tomentosa (Willd. ex Schult.) DC., a plant native to the Amazon region, is used widely in popular medicine and by the pharmaceutical industry because of its anti-inflammatory activity. However, the survival of this species is endangered by deforestation and indiscriminate collection, and a preservation plan is urgently required. The objectives of this study were to determine the genetic and chemical variability between and within eight populations of U. tomentosa from the Brazilian states of Acre, Para and Amapa, and to investigate possible correlations between genetic and geographical distances, and between geographical distances or altitude and the accumulation of bioactive oxindole alkaloids. Three sequence-related amplified polymorphism (SRAP) markers were employed to fingerprint genomic DNA, and the amounts of mitraphylline and isomitraphylline in leaf samples were established by high-performance liquid chromatography. Although significant divergence existed between the tested populations (F-ST = 0.246), the largest genetic diversity and the highest percentage of polymorphism (95.68%) was found within the population from Mancio Lima, Acre. Gene flow was considered rather limited (Nm = 1.57), and no correlations between genetic and geographical distances were detected, suggesting that population structure followed an island model. Accumulations of mitraphylline and isomitraphylline varied in the range 32.94 to 0.57 and 3.75 to 0.36 mg g(-1) dry weight, respectively. The concentration of isomitraphylline was positively influenced by altitude, such that the population collected at the site with the highest elevation (Tarauaca, Acre) exhibited the greatest alkaloid content. SRAP markers were very efficient in fingerprinting genomic DNA from U. tomentosa populations and clearly showed that genetic variability within populations was greater than between populations. A conservation and management plan should prioritize the creation of germplasm banks to prevent the loss of existing genetic variability, particularly within alkaloid-rich populations such as those of Tarauaca